Enamel Hardness Differences After Topical Application Of Theobromine Gel And Casein Phosphopeptide-Amorphous Calcium Phosphate - Tamara Yuanita; Nanik Zubaidah; Mifta Izha A R (Universitas Airlangga, 2020)
Background: Most soft drinks contain citric acid / phosphoric acid with pH <3.5. Strong acids in the oral cavity cause tooth erosion. Tooth erosion leads to demineralization enamel. Remineralization can prevent demineralization process. One of the commercial remineralization agents is Casein Phosphopeptide-amorphous Calcium Phosphate(CPP-ACP) but it has low solubility and less affordable price. Therefore, a natural ingredients such as theobromine from cocoa extract need to be developed as remineralization agent. Objective: To determine enamel hardness differences due to topical application of theobromine gel and CPP-ACP. Method: incisive crowns were cut off (1x1) cm then planted in cylindrical acrylic resin. All samples were immersed with citric acid for 90 minutes then divided into 3 groups. Group I (control) was immersed with aquades (96 min), group II was applied with theobromin gel 200 mg/l (96 min), group III was applied with CPP-ACP (96 min). By using vickers hardness tester, enamel hardness be measured (15 sec) at 3 points. Results: There were significant differences between the control group, CPP-ACP group, and theobromine gel group. Conclusion: Enamel hardnesse with theobromine gel application is higher than CPP-ACP application..